Changes in Miombo woodland cover in and around Sengwa Wildlife Research area, Zimbabwe, in relation to elephants and fire - Mapaure, I.; Campbell, Bruce M. (2002)
One of the consequences of impacts of elephants and fire on woodlands is a change in woody cover, which often results in major challenges for wildlife managers. Changes in miombo woodland cover in and around Sengwa Wildlife Research Area (SWRA) between 1958 and 1996 were quantified by analyzing aerial photographs. Woody cover in SWRA decreased from 95.2% in 1958 to 68.2% in 1996, with a lowest mean of 62.9% in 1983. The annual absolute rate of woody cover change in SWRA increased from -1.1% perannum between 1993 and 1996, while the annual relative rate increased from -1.1% per annum between 1958 and 1964 to 3.3% per annum between 1993 and 1996. There was a strong negative correlation between elephant densities and woody cover in SWRA, suggesting that loss of woody cover was mainly due to elephants. Woodland recovery after 1983 was due to reductions in elephant populations through legal and illegal off-take and reductions in fire frequency. Surrounding areas experienced less woody cover losses than SWRA, mainly due to tree removal by locals whose densities increased after the eradication of tsetse fly in the 1970s.